Is the incidence of rheumatoid arthritis rising? Results from Olmsted County, Minnesota, 1955-2007 - Myasoedova, Elena (2010)
OBJECTIVE: To examine the trends in incidence and prevalence of rheumatoid arthritis (RA) from 1995 to 2007. METHODS: To augment our preexisting inception cohort of RA patients (1955-1994), we assembled a population-based incidence cohort of individuals aged ≥18 years who first fulfilled ACR 1987 criteria for RA between 1/1/1995 and 12/31/2007 and a cohort of patients with prevalent RA on 1/1/2005. Incidence and prevalence rates were estimated and were age- and sex-adjusted to the 2000 US whites. Trends in incidence rates were examined using Poisson regression methods. RESULTS: The 1995-2007 incidence cohort comprised 466 patients (mean age 55.6 years; 66% female; 69% rheumatoid factor positive). The overall age- and sex-adjusted annual RA incidence was 40.9/100,000 population. The age-adjusted incidence in women was 53.1/100,000 population,(in men: 27.7/100,000 population). During 1995-2007 there was a moderate increase in RA incidence in women (p=0.02), but not in men (p=0.74). The increase was similar among all age groups. The overall age- and sex-adjusted prevalence on 1/1/2005 was 0.72% (95% CI 0.66–0.77) up from 0.62% (95% CI 0.55–0.69) in 1995 (p<0.001). Applying the 1/1/2005 prevalence to the US 2005 population, an estimated 1.5 million US adults are affected by RA. This is up from the 1.3 million reported previously. CONCLUSION: The incidence of RA appears to be rising in women during 1995-2007 period. The reasons for this recent increase in incidence are unknown, but environmental factors may play a role. A corresponding increase in prevalence of RA was also found.